Direct Delivery of Antisense Oligonucleotides to the Middle and Inner Ear Improves Hearing and Balance in Usher Mice - Lentz, Jennifer J. (Mol Ther, 2020)
Usher syndrome is a syndromic form of hereditary hearing impairment that includes sensorineural hearing loss and delayed-onset retinitis pigmentosa (RP). Type 1 Usher syndrome (USH1) is characterized by congenital profound sensorineural hearing impairment and vestibular areflexia, with adolescent-onset RP. Systemic treatment with antisense oligonucleotides (ASOs) targeting the human USH1C c.216G>A splicing mutation in a knockin mouse model of USH1 restores hearing and balance. Herein, we explore the effect of delivering ASOs locally to the ear to treat hearing and vestibular dysfunction associated with Usher syndrome. Three localized delivery strategies were investigated in USH1C mice: inner ear injection, trans-tympanic membrane injection, and topical tympanic membrane application. We demonstrate, for the first time, that ASOs delivered directly to the ear correct Ush1c expression in inner ear tissue, improve cochlear hair cell transduction currents, restore vestibular afferent irregularity, spontaneous firing rate, and sensitivity to head rotation, and successfully recover hearing thresholds and balance behaviors in USH1C mice. We conclude that local delivery of ASOs to the middle and inner ear reach hair cells and can rescue both hearing and balance. These results also demonstrate the therapeutic potential of ASOs to treat hearing and balance deficits associated with Usher syndrome and other ear diseases.